Highly purified hypochlorous acid water facilitates glucose metabolism and memory formation in type 2 diabetic mice associated with altered-gut microbiota - Kazuki Watanabe; Yusuke Maruyama; Risako Mikami; Keiji Komatsu; Kenji Kikuchi; Kunimoto Hotta; Toshikazu Yoshikawa; Kouetsu Ogasawara; Atsuhiko Hattori; Shinichi Arakawa (Scientific Reports, 2024)
Abstract Hypochlorous acid (HOCl) is an endogenous oxidant and chlorinating agent in mammals that is effective against a broad range of microorganisms. However, the effects of exogenous HOCl on biological processes have not been reported. In this study, the effects of highly purified slightly acidic hypochlorous acid water (HP-HAW) were investigated. After the safety of oral administration of HP-HAW was confirmed, the effects of HP-HAW on glucose homeostasis were assessed in mice. HP-HAW treatment significantly improved blood glucose levels in hyperglycemic condition. Based on the 16S rRNA sequencing, HP-HAW treatment significantly increased the diversity and changed the composition of gut microbiota by decreasing the abundance of genus Romboutsia in mice fed normal chow. In obese mice, HP-HAW administration tended to improve glucose tolerance. HP-HAW also attenuated memory impairments and changes N-methyl-d-aspartate (NMDA) receptor mRNA expression in obese mice. HP-HAW treatment suppressed Il-6 mRNA expression in the hippocampus in type 2 diabetic mice. Overall, these results support HP-HAW as a potential therapeutic agent to improve or prevent glucose tolerance and memory decline via gut microbiota alteration.